Banking in the Mediterranean: Financing needs and opportunities in turbulent times - Geoffrey Frewer; Frank Betz; Sarah Stölting (European Investment Bank (EIB), 2013)
This study explains the latest developments of the banking sectors in Mediterranean Partner Countries and discusses financing needs and opportunities that arise in these turbulent times. Its aim is to contribute to a better understanding of recent market developments as well as a to provide a useful reference text on banking in the region.
Keywords: 330